ACTUAL ASPECTS OF EDUCATIONAL AND PRACTICAL ENDODONTIC PHANTOM USAGE MADE OF TRANSPARENT EPOXY RESIN WITH THE AIM OF IMPROVING EDUCATIONAL AND PRACTICAL TRAINING OF THE STUDENTS IN DENTISTRY - Герелюк, В. І.; Матвійків, Т. І.; Ільків, М. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The article deals with the peculiarities of working out practical skills by third-year students of the department of dentistry in the section of "Endo-dontics". The model of the endodontic phantom made of the transpa-rent epoxy resin will help to clearly reproduce the clinical situation individually recomended for each student. The simulation of clinical situations by the student in person will be accomplished accordingly to the recommendations of the teacher. The reproduction of the possible anatomical variants of teeth root canal system, using an endodontic phantom, made from a transparent epoxy resin, will provide an ability to trace the movement of the endodontic instrument in the course of simulated and unlimited variants of the anatomical features of the root canals. It will improve the ability to practice manual skills by students when working with a variety of endodontic instruments.